Effectiveness of emetics to study plastic ingestion by Leach's Storm-petrels (Oceanodroma leucorhoa) - Bond, AL; Jennifer Lavers (2013)
Most plastic ingestion studies rely on dissection of dead birds, which are found opportunistically, and may be biased. We used Leach’s Storm-petrels (Oceanodroma leucorhoa) in Newfoundland to study the effect of dose volume, and the efficacy of emesis using syrup of ipecac as an emetic. Ipecac is a safe method of non-lethally sampling stomach contents, and recovered all ingested plastic. Almost half the storm-petrels sampled had ingested plastic, ranging from 0 to 17 pieces, and weighing 0.2–16.9 mg. Using the Ecological Quality Objective for Northern Fulmars, adjusted for storm-petrels smaller size, 43% exceeded the threshold of 0.0077 g of plastic. Many adult seabirds offload plastic to their offspring, so storm-petrel chicks likely experience a higher plastic burden than their parents. The ability to study plastic ingestion non-lethally allows researchers to move from opportunistic and haphazard sampling to hypothesis-driven studies on a wider range of taxa and age classes.